2004
DOI: 10.1590/s0004-282x2004000300014
|View full text |Cite
|
Sign up to set email alerts
|

Eletrencefalograma quatitativo em crianças com epilepsia benigna da infância com pontas centrotemporais: análise de freqüências

Abstract: RESUMO -Abordaram-se parâmetros quantitativos do eletrencefalograma em crianças com epilepsia benigna da infância com pontas centrotemporais (EBICT). Foram estudadas 27 crianças com diagnósticos de EBICT. Foi realizado o eletrecenfalograma durante vigília, em repouso, e selecionadas cerca de 20 janelas com 2,56 s. Foram calculados os valores de potência absoluta e relativa nas faixas delta, teta, alfa e beta. Os resultados foram comparados aos de 27 crianças sadias pareadas quanto a idade e escolaridade matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…The present study showed diffuse alterations in the absolute and relative theta powers, as already mentioned in the literature. 2,3 Such findings indicate diffuse functional modifications, not simply restricted to the regions involved in the epileptiform activity. One hypothesis to explain these alterations is that they are a result of maturational disturbances in the electrical activity, 2,3 since in normative EEG studies with normal children, progressive decreases in the absolute and relative powers in the delta and alpha bands were found, with increase in age.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The present study showed diffuse alterations in the absolute and relative theta powers, as already mentioned in the literature. 2,3 Such findings indicate diffuse functional modifications, not simply restricted to the regions involved in the epileptiform activity. One hypothesis to explain these alterations is that they are a result of maturational disturbances in the electrical activity, 2,3 since in normative EEG studies with normal children, progressive decreases in the absolute and relative powers in the delta and alpha bands were found, with increase in age.…”
Section: Discussionmentioning
confidence: 96%
“…In a specific study with children suffering from BECTS, in addition to the increase in absolute power in various frequency bands, an increase in the relative theta power was observed. 3 Thus, although EA is indeed focal in BECTS, the observation of diffuse alterations of BA in the qEEG suggests broader functional modifications, which could be related to brain immaturity. 2 On the other hand, discreet alterations in neuropsychological functions have been described in children with BECTS, which could, on occasions, interfere with school performance.…”
Section: Introductionmentioning
confidence: 90%
“…On the one hand, it is considered that the lesions caused by the manifestations of epileptic seizures are on a developing brain (Overvliet et al, 2013, Smith et al, 2012, suggesting that the reading difficulties presented by children with RE are directly associated with the amount of nocturnal epileptiform activity (Gobbi, Boni, & Filippini, 2006). On the other, there is the occurrence of overlapping cortical areas of language with epileptic activity in the central region, namely the rolandic and Sylvian regions (Fonseca et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This is because this area is considered to be the main weakness in the cognitive functions of this clinical subgroup, which is possibly associated to the harm caused by epilepsy crises on a developing brain (Aquino, Montenegro, Guerreiro & Guerreiro, 2005;Flax et al, 2003;Overvliet et al, 2013;Smith et al, 2012), especially on the areas of the brain related to language: the center of the brain, predominantly in the lower portion of the rolandic and Sylvian areas (Fonseca, Tedrus, Chiodi, Cerqueira & Duran, 2004;Hommet et al, 2001;Staden, Isaaca, Boyd, Brandl &, 1998;Xiao et al, 2016;Zaninotto & Hamad, 2012).…”
Section: Introductionmentioning
confidence: 99%